Strategies For Translating Metaphorical Collocations In The Holy Qur’an - Alshaje’a, Hilal (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
A lot of research addresses to the definitions of collocations, their properties, and how they are different from other language forms like metaphors and idioms concerning the transparency of its adjacent constituents in contributing to meaning, both intra- and interlingually. Collocations in all languages including in Arabic, reflect conventional uses and fixed patterns, but the Qur’anic collocations show distinguished uses that are different from those existed in other Arabic genres. Thus, translating Qur’anic collocations in particular brings about a challenge because of linguistic, cultural, and communicative reasons. The present paper clarifies the distinguished characteristic of collocation in the Qur’an that makes its discourse incomparable in other languages such as English, and discusses the most appropriate strategies for rendering metaphorical collocations in the Holy Qur’an as well. Some translations of the Qur’anic text including collocation have been chosen as they display linguistic problems produced by cling on the part of the translators to the word order of the Arabic source text, thus causing eccentricity in the target language.